Oral cancer: the role of the dentist in early diagnosis and control - Rocha-Buelvas, Anderson (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This paper emphasizes the importance of early detection of oral cancer as a prevention and control tool. It begins documenting the epidemiology and relevance in public health of this type of cancer by means of scientific evidence which demonstrates that, compared to other types of cancer, it is not statistically significant. Oral cancer is more aggressive and lethal than other tumors. Besides, it has multiple etiologic factors, high metastasis potential, cumulative effect with time and, it compromises esthetics and function of the patients. Subsequently, it ratifies that oral cancer must be prevented and controlled by means of instruction on risk factors, early detection and sufficient clinical and epidemiological update. The last part of the paper analyzes the importance of early diagnosis of oral cancer especially considering the persistent lack of teaching in education and prevention in most dental schools; dentists usually diagnose oral cancer in the late stages. Finally, the unsatisfactory primary and secondary prevention of oral cancer is questioned.